Leaving-home transition and later parent–child relationships: proximity and contact in Italy. Issue 1 (1st January 2017) - Tosi, Marco
ABSTRACT: Previous research points out that early life-course transitions affect subsequent parent–child relationships. This study examines the association between the leaving-home transition and later parent–child relations in Italy, by taking into account different timings and reasons to move out of the parental home. Using pooled data from two waves (2003 and 2009) of the Family and Social Subject Survey, Ordered Logistic regression models were adopted to analyze residential proximity and face-to-face contact between parents and their adult children. The findings show that the longer the time adult children spent in their parents' home, the higher the propensity to reside near, and maintain frequent interaction with parents in later life is. Spending longer time in the parental home seems to provide much less benefit for daughters than for sons. The positive association between co-residence duration and later parent–daughter relations decreases until disappearing in concomitance with the normative age for leaving home. Considering the reasons for leaving home, adult children moving out to get married tend to have more intense intergenerational ties. Marriage continues to be the normative occasion to leave the parental family, particularly among adult daughters, who are subject to greater cultural expectations about family ties.